The Effect of Income Tax Policy on Foreign Direct Investment: Panel Data Analysis in Developing Countries - Loso Judijanto; Syahriati Fakhriah; Xie Guilin; Nurjanna Ladjin; Ahmad Rizani (Rechtsnormen: Journal of Law, 2024)
Background. Research Background Foreign direct investment (FDI) is an important component in accelerating the economic growth of developing countries. As competitive tax rates can be an important factor in foreign investors' investment location selection, income tax policy has been the focus of attention in an effort to attract FDI. However, the real impact of these tax policies on foreign direct investment flows in developing countries is still in doubt. Purpose. This study aims to understand whether a reduction or increase in income tax rates has a significant impact on the amount and flow of foreign direct investment in developing countries, using panel data analysis. This research is expected to enhance the understanding of the role of tax policy in attracting FDI and its implications for the economic growth of developing countries. Method. This study aims to understand whether a reduction or increase in income tax rates has a significant impact on the amount and flow of foreign direct investment in developing countries, using panel data analysis. This research is expected to enhance the understanding of the role of tax policy in attracting FDI and its implications for the economic growth of developing countries. Results. The analysis shows that developing countries' income tax policies and foreign direct investment are closely linked. The main results show that a reduction in income tax rates tends to increase foreign investment inflows, while an increase in rates can have the opposite effect. In addition, the interaction between tax policy and other economic components, such as political stability and infrastructure, also affects the impact of tax policy on FDI. Conclusion. This study shows that income tax policy plays an important role in determining the level of foreign direct investment in developing countries. Developing countries can increase foreign investment flows by lowering income tax rates. However, to create an effective policy, it is also necessary to consider other aspects such as political stability, regulation, and infrastructure.